Magnetite NPs@C with Highly-Efficient Peroxidase-Like Catalytic Activity as an Improved Biosensing Strategy for Selective Glucose Detection - Arana, Mercedes (2014)
This work reports the novel application of carbon-coated magnetite nanoparticles (mNPs@C) as catalytic nanomaterial included in a composite electrode material (mNPs@C/CPE) taking advantages of their intrinsic peroxidase-like activity. The nanostructured electrochemical transducer reveals an enhancement of the charge transfer for redox processes involving hydrogen peroxide. Likewise, mNPs@C/CPE demonstrated to be highly selective even at elevated concentrations of ascorbic acid and uric acid, the usual interferents of blood glucose analysis. Upon these remarkable results, the composite matrix was further modified by the addition of glucose oxidase as biocatalyst, in order to obtain a biosensing strategy (GOx/mNPs@C/CPE) with enhanced properties for the electrochemical detection of glucose. GOx/mNPs@C/CPE exhibit a linear range up to 7.5×10−3 mol L−1 glucose, comprising the entirely physiological range and incipient pathological values. The average sensitivity obtained at −0.100 V was (1.62±0.05)×105 nA L mol−1 (R2=0.9992), the detection limit was 2.0×10−6 M while the quantification limit was 6.1×10−6 mol L−1. The nanostructured biosensor demonstrated to have an excellent performance for glucose detection in human blood serum even for pathological values.